The Role of In-Service Teacher in Supervising Pre-Service Teachers during Teaching Practicum Program - Latifah, Diah (Harmonia: Journal of Arts Research and Education, 2014)
This study analyzes the role of in-service teacher in supervising the pre-service teachers during the Teaching Practicum Program and in building the pre-service teachers’ character to be competent music teachers in the future. This study implements narrative inquiry as the method of research. Narrative inquiry method explains the variety of cases during the process of supervision by the in-service teacher. In addition, the research was held in Pasundan 8 Senior High School Bandung and was analyzed further by using qualitative methods with interactive analysis as it is formulated in the research question of this study. Results show that the supervision by an in-service teacher has been successfully enhanced the ability of pre-service teachers in teaching art and culture, particularly music lesson. The competence of pre-service teachers can be achieved by giving them examples, model, and music experience from in-service of the pre-service teachers.